The Effects of Safety Management Systems, Attitude and Commitment on Safety Behaviors and Performance - Wen-Jywan Su (International Journal for Applied Information Management, 2021)
Safety culture is part of organizational culture, and assessing corporate safety culture as a means of increasing safety performance is gaining acceptance. Based on Cooper’s reciprocal model, this paper studied the effects of managerial safety commitment and workers’ personal safety attitude as well as the organization safety management system (SMS) towards individual safety compliance and participation, and their relationship with safety performance. Questionnaires were obtained from employees and contractors of a large steel company in 14 functional departments. Modified reciprocal safety models were verified by structural equation model (SEM). The SMS and personal attitude have effects on compliance behavior. Participation behavior was influenced by the SMS and management commitment. Perceived performance was affected by compliance and participation behavior and management commitment as well. Successful implementation of a SMS will strongly motivate the workers’ participation in safety activities and compliance with safety regulation. Managers’ strong commitment toward safety is essential to foster safety performance. A Good safety attitude will motivate the worker to follow safety regulations for self-protection but does not encourage him to participate in safety activities. Increasing managerial safety commitment such as concerns about workers’ safety participation activities and participation safety activities will directly motivate the worker’s safety participation.